Impact of an augmented reality system on students' learning performance for a health education course - Ya-Ming Shiue; Yu-Chiung Hsu; Meng-Huei Sheng; Cheng-Hsuan Lan (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
In recent years, the innovative applications of integrated augmented reality (AR) into educational settings had increased rapidly in Taiwan. AR provides the scene of the real world while interacting with the virtual and physical objects and increases students' learning motivation. This paper presents an empirical study that investigated the middle-school students learning health education courses related to human body structure knowledge integrating AR technology with different learning style preferences. A two-way t-test was applied to examine the experimental (AR-based) or control (traditional lecture) group in health education courses for four consecutive weeks, comparing with pre-test and post-test scores. The findings revealed that students in the AR experimental group apparently had a higher learning achievement than the students in the control group. Moreover, students with different learning styles had the significant differences in learning achievement. The research outcomes provided the practical implications for educators in incorporating AR applications for enhancing learning motivation and to study the differences in students' learning style.
Keywords: D83; I10; I23; 330; Augmented reality; learning style; learning achievement; health education; human body structure